Expression of caspases 3, 6 and 8 is increased in parallel with apoptosis and histological aggressiveness of the breast lesion - Vakkala, M (Nature Publishing Group, 1999)
The aim of this investigation was to study the expression of caspases 3, 6 and 8 and their association to apoptosis in preneoplastic and neoplastic lesions of the breast. The material consisted of nine benign breast epithelial hyperplasias, 15 atypical hyperplasias, 74 in situ and 82 invasive carcinomas. The extent of apoptosis was assessed by the TUNEL method and caspase 3, 6 and 8 expression by immunohistochemistry with specific antibodies. Increased caspase 3 immunopositivity, as compared to staining of normal breast ductal epithelium, was seen in 22% of benign epithelial hyperplasias, 25% of atypical hyperplasias, 58% of in situ carcinomas and 90% of invasive carcinomas. The corresponding percentages for caspase 6 and 8 were 11%, 25%, 60%, 87% and 22%, 57%, 84%, 83% respectively. In high-grade in situ lesions there were significantly more cases with strong caspase 3, 6 and 8 immunoreactivity than in low- and intermediate-grade lesions (P = 0.0045, P = 0.049 and P = 0.0001 respectively). In invasive carcinomas, however, no association between a high tumour grade and caspase 3, 6 or 8 expression was found (P = 0.27, P = 0.26 and P = 0.69 respectively). The mean apoptotic index was 0.14 ± 0.14% in benign epithelial hyperplasias, 0.17 ± 0.12% in atypical hyperplasias, 0.61 ± 0.88% in in situ carcinomas and 0.94 ± 1.21% in invasive carcinomas. In all cases strong caspase 3, 6 and 8 positivity was significantly associated with the extent of apoptosis (P < 0.001, P = 0.015 and P = 0.050 respectively). The results show that synthesis of caspases 3, 6 and 8 is up-regulated in neoplastic breast epithelial cells in parallel to the increase in the apoptotic index and progression of the breast lesions. © 1999 Cancer Research Campaign